The impact of environmental accidents on the green apparel purchase behavior of Generation Z - Liu, Lixian; Zhang, Wenwen; Li, Hao; Zheng, Zeyu (Frontiers in Psychology, 2024)
Introduction This study examines the impact of environmental accidents on Generation Z’s purchase behavior towards green apparel, integrating the Theory of Planned Behavior and the Norm Activation Theory to conceptualize how different dimensions of environmental accidents influence consumer behavior. Methods Employing focus groups and questionnaires, this research captures data on Generation Z’s perceptions and behaviors towards green apparel in the context of environmental accidents. The collected data were analyzed using SPSS software, with structural equation modeling employed to test the research hypotheses. Results The findings indicate that the scale (H12 = 0.545), the degree of suddenness (H18 = 0.357), nature of the effect (H14 = 0.295), and duration (H17 = 0.289) of environmental accidents significantly influence Generation Z’s awareness of consequences, behavioral attitudes, subjective norms, and perceived behavioral control regarding the purchase of green clothing. Notably, the scale of environmental accidents has a significant impact on perceived behavioral control, which in turn significantly affects Generation Z’s intention to purchase green apparel (H3 = 0.5). Discussion This study elucidates the impact of environmental accidents on Generation Z’s green apparel purchase intentions. The findings highlight Generation Z’s environmental awareness and social responsibility, influencing their purchasing decisions. This research offers practical insights for brands to enhance green marketing strategies, focusing on product quality, transparency, and consumer education to align with Generation Z’s values and expectations. Future research should explore additional factors affecting purchase behavior and strategies to bridge the intention-behavior gap.